A Case Study On Iran Air Tours (IRAT) - Menhaj, Amir Mohammad (2008)
The objective of this case study are to study overall performance of IRAT till the end of the year 2006, to evaluate and discuss IRAT's strength and weaknesses and to offer suggestions for the future development of IRAT based on the study of its business environment and internal analysis. The proposed strategies will aid IRAT to create opportunities for success ful and profitable business solutions in the Iran's airline industry.